1996
DOI: 10.1039/dt9960002815
|View full text |Cite
|
Sign up to set email alerts
|

Neutral five-co-ordinate gallium(III) and indium(III) complexes derived from sulfur ligands

Abstract: Five-co-ordinated gallium(iir) and indium(ii1) complexes, GaCl[PhC(S)CHC(O)Ph],, GaCI(S,CNR,),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 37 publications
2
24
1
Order By: Relevance
“…The two shorter Ga-S distances in each molecule are comparable (av. 2.317 Å ) and are well within the single Ga-S bond [14,30]. However, this distance is smaller than the one reported for [[Ga{S 2 CN(CH 2 CH 2 ) 2 O} 3 ] (av.…”
Section: Structure Of [Mega(s 2 Ctol) 2 ]contrasting
confidence: 70%
“…The two shorter Ga-S distances in each molecule are comparable (av. 2.317 Å ) and are well within the single Ga-S bond [14,30]. However, this distance is smaller than the one reported for [[Ga{S 2 CN(CH 2 CH 2 ) 2 O} 3 ] (av.…”
Section: Structure Of [Mega(s 2 Ctol) 2 ]contrasting
confidence: 70%
“…Work by Nöth has demonstrated that the sodium salt of the structurally not too dissimilar benzoyl(thiobenzoyl)methane, Na + [PhC(S)CHC(O)Ph] − , reacts with GaCl 3 irrespective of the molar ra- Scheme 1. tio used to afford the galliumchlorido(III) species [GaCl{PhC(S)CHC(O)Ph} 2 ] containing two deprotonated ligands [24]. Their interpretation for this observation and also for the fact that the chlorido ligand in the compound is kinetically inert was based on steric effects.…”
Section: Resultsmentioning
confidence: 99%
“…The gallium and indium atom in [MCl(S 2 CNR 2 ) 2 ] lie above (0⋅46 Å for Ga and 0⋅79 Å for In) the mean S 4 plane of a distorted square pyramidal configuration. 49 The crystals of [MeGa(S 2 Ctol) 2 ] have two crystallographically independent molecules. The two asymmetrically chelated dithiocarboxylate ligands differ significantly in each molecule.…”
Section: Structuresmentioning
confidence: 99%
“…24 Unlike organometallic derivatives, the chloro complexes, [MCl 3-n {S 2 P(OR)} n ] (n = 1 or 2), display molecular ion peaks in their mass spectra. 20,21 The M-S stretching in the IR spectra of a variety of complexes have been assigned in the regions of 310-352 (M = In) 49 and 365-380 cm -1 (M = Ga). 33 The Ga-C and In-C stretching vibrations appear in the regions 530-606 33,35 and 450-521 cm -1 33,37 respectively.…”
Section: Synthesesmentioning
confidence: 99%
See 1 more Smart Citation